MENGEMBALIKAN KEBERMAKNAAN TRI PUSAT PENDIDIKAN PADA LEMBAGA PENDIDIKAN - Muliati, Binti (Jurnal al Hikmah, 2016)
Local wishdom, the learner starts and empties, are often overlooked in the implementation of educational policy-oriented science and technology development and readiness to face the globalization era. As a result, learning materials obtained in school becomes less meaningful in real life learners and set them up for life, life, and the real livelihood. In fact, should the results and the function of education is able to identify, explore, develop, and empower the potential of learners in facing the future and the future of the nation and not vice versa -empowering potential learners with tasks that are less meaningful. From this, the need for the return of the spirit of education needs to be headed by synergizing the meaningfulness of family education, schools, and society as taught by Ki Hajar Dewantara called tripusat education. This paper will review the descriptive analytical extent of the importance of restoring the function and role of the central tri education as taught Ki Hajar Dewantara